Legal Analysis of the Impact of Nusantara Capital Development on Environmental Damage - Wilibaldus Jampa; Donna Ramadhan Fitri (Yayasan Lembaga Studi Makwa, 2024)
The development of Nusantara as Indonesia's new capital in East Kalimantan has sparked various reactions, particularly regarding its environmental impact. This study aims to analyze the legal implications of this development on environmental degradation and to evaluate the measures that have been taken to mitigate these impacts. By using a normative juridical approach and document analysis, this research examines the relevant legislation related to environmental protection and sustainable development, and compares it with the practices occurring on the ground. The findings reveal that, despite a robust regulatory framework theoretically designed to safeguard the environment, there is a substantial gap between policy and practice. This disconnect is evident in several key areas: the frequent bypassing of mandatory Environmental Impact Assessments (EIA), non-compliance with sustainable land use standards, and a general lack of accountability for environmental violations. Such shortcomings have led to alarming rates of deforestation, loss of biodiversity, and long-term ecological damage, undermining the very principles of sustainable development that the project purports to uphold. This research underscores the urgent necessity for enhanced legal and regulatory measures to ensure that the development of Nusantara not only achieves its economic and social objectives but also preserves the environmental integrity of the region. The study provides valuable policy recommendations aimed at bridging the gap between environmental protection and development, offering a pathway towards a more sustainable and legally compliant future for Indonesia’s new capital.